Threat of death and autobiographical memory: a study of passengers from Flight AT236 - McKinnon, Margaret C. (Clin Psychol Sci, 2014)
We investigated autobiographical memory in a group of passengers onboard a trans-Atlantic flight that nearly ditched at sea. The consistency of traumatic exposure across passengers, some of whom developed post-traumatic stress disorder (PTSD), provided a unique opportunity to assess verified memory for life-threatening trauma. Using the Autobiographical Interview, which separates episodic from non-episodic details, passengers and healthy controls (HCs) recalled three events: the airline disaster (or a highly negative event for HCs), the September 11, 2001 attacks, and a non-emotional event. All passengers showed robust mnemonic enhancement for episodic details of the airline disaster. Although neither richness nor accuracy of traumatic recollection was related to PTSD, production of non-episodic details for traumatic and non-traumatic events was elevated in PTSD passengers. These findings indicate a robust mnemonic enhancement for trauma that is not specific to PTSD. Rather, PTSD is associated with altered cognitive control operations that affect autobiographical memory in general.